Short‐term risk assessment of botnet attacks on advanced metering infrastructure. Issue 3 (5th September 2017) - Sgouras, Kallisthenis I.; Kyriakidis, Avraam N.; Labridis, Dimitris P.
Abstract : An ongoing evolution of the power grids into more intelligent and sophisticated ones has been taking place since the beginning of the 21st century. The underlying objective of the power systems is to deliver electrical energy with high‐security standards, i.e. to supply power to the consumers uninterruptedly. However, the integration of information technology into the smart grid introduces new vulnerabilities related to cyber‐security which the authors should address extensively. This study discusses the impact of coordinated cyber‐attacks on the advanced metering infrastructure. In this work, emulations of distributed denial‐of‐service attacks in a closed testbed environment using a topology of smart meters that participate in an electricity market are being performed. This study proposes a method to evaluate the impact on the reliability of such attacks. The results demonstrate that the proposed method can serve as a tool for the evaluation of the short‐term risk of botnet attacks during load shifting in smart distribution networks.